2022
DOI: 10.1017/s0031182022001275
|View full text |Cite
|
Sign up to set email alerts
|

Ceratonova shasta: a cnidarian parasite of annelids and salmonids

Abstract: The myxozoan Ceratonova shasta was described from hatchery rainbow trout over 70 years ago. The parasite continues to cause severe disease in salmon and trout, and is recognized as a barrier to salmon recovery in some rivers. This review incorporates changes in our knowledge of the parasite's life cycle, taxonomy and biology and examines how this information has expanded our understanding of the interactions between C. shasta and its salmonid and annelid hosts, and how overarching environmental factors affect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 92 publications
0
11
0
1
Order By: Relevance
“…Adaptive immune response genes (IgT and IgM) were also associated with pathogen abundance in sentinel salmon. Prior work exploring antibody response in salmon and myxozoan infection (the two main pathogens found in this study) remains unresolved but generally observed that fish susceptible to infection to have less upregulation of IgT and IgM compared with resistant fish ( Barrett et al , 2021 ; Bartholomew et al , 2022 ). Recently however, Taggart-Murphy et al (2021) unexpectedly observed that IgT and IgM were upregulated in intestinal tissue in susceptible rainbow trout as early as 7 days post-exposure and suggested that in acute high mortality cases the immune response, while mounted, may be insufficient or be too late to protect the host.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Adaptive immune response genes (IgT and IgM) were also associated with pathogen abundance in sentinel salmon. Prior work exploring antibody response in salmon and myxozoan infection (the two main pathogens found in this study) remains unresolved but generally observed that fish susceptible to infection to have less upregulation of IgT and IgM compared with resistant fish ( Barrett et al , 2021 ; Bartholomew et al , 2022 ). Recently however, Taggart-Murphy et al (2021) unexpectedly observed that IgT and IgM were upregulated in intestinal tissue in susceptible rainbow trout as early as 7 days post-exposure and suggested that in acute high mortality cases the immune response, while mounted, may be insufficient or be too late to protect the host.…”
Section: Discussionmentioning
confidence: 86%
“…It is unknown if the infected fish we observed would have transitioned into a diseased state over time, or if they would have cleared the infection. Adding additional complexity to the interpretation of pathogen detection is that there are three genotypes (0, I, and II) of C. shasta , and only genotype I can cause disease in Chinook salmon ( Bartholomew et al , 2022 ). Unpublished data from our group screening environmental water samples from the Sacramento River have primarily detected genotype I by sequencing, and histology results from this study support this finding.…”
Section: Discussionmentioning
confidence: 99%
“…Ceratonova shasta is well recognized as a cause of intestinal lesions and morbidity in juvenile salmonids in the Pacific Northwest (Bartholomew et al., 2022), and hence it was a top candidate for a potential cause of the loss of EI. However, this parasite was actually positively correlated with EI, and was not observed in most of the fish with EI scores of <50%.…”
Section: Discussionmentioning
confidence: 99%
“…The progression of infection and pathogenesis of C. shasta in juvenile fish is quite different from those in adult Chinook Salmon. In contrast to rapid development and death (weeks) in juveniles (Bartholomew et al., 2022), in most adult salmon the parasite does not sporulate until spawning or after spawning and death (Kent et al., 2014). Ceratonova shasta was prevalent in the Round Butte fish which had severe disease, whereas the parasite was not seen in the White River fish (all with normal intestines).…”
Section: Discussionmentioning
confidence: 99%
“…The myxozoan Ceratonova shasta causes severe disease in salmon and trout in most major river systems of the Pacific Northwest of the United States and British Columbia, Canada, including the Sari Joaquin, Sacramento, Pit, Klamath, Rogue, Columbia and Fraser Rivers (Hallett and Bartholomew, 2012). Jerri Bartolomew with 3 co-authors from the USA and 1 from the Czech Republic/Spain presented a review that incorporates changes in our knowledge of the parasite's life cycle, taxonomy and biology of C. shasta (Bartholomew et al ., 2022). The authors focus on the interactions between this pathogenic myxozoan and its salmonid and annelid hosts, profiting from the establishment of the C. shasta life cycle in the laboratory and the availability of transcriptomic data.…”
Section: Scope Of the Special Issuementioning
confidence: 99%